Reproductive biology of Clerodendrum splendens (Verbenaceae) - Gautam, Prem Kumar; Rohitash, Rohitash (Journal of Experimental Sciences, 2013)
Clerodendrum splendens (Verbenaceae) is an ornamental climbing shrub. Flowering occur during the period between December – April. Flowers are red, small complete pedicellate, pentamerous, zygomorphic, hermaphrodite and hypogynous. Anthesis occur between 06:00 – 06:30hrs followed by anther dehiscence at 07:00 – 09:00hrs. Stigma become receptive at 11:00 – 14:00hrs. There are 2160 ± 380 pollens/flower. There are 4 ovules/flower and pollen – ovule ratio is 540 : 1. Nearly 2% flower show open pollination. There is no fruitset in bagged inflorescence indicating cross pollinating nature. Fruit and seedset percentage is very low. Xylocopa Eumenes sp. and Componotus campertris (Black ant) are most effective visitors.